2006
DOI: 10.1007/bf03256457
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Gene Expression Response to Acute Indomethacin Exposure

Abstract: These data confirmed that even brief exposure to indomethacin altered serum enzymatic activities and that high levels significantly altered gene expression in the liver and hepatic histology (by interfering with the clearance of toxins and xenobiotic substrates) and the regulation of basal metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Although FO is a well-known lipid-lowering agent, the effect of Indo in modulating lipid metabolism has not been clearly elucidated. As for hepatic steatosis, Indo was shown to increase hepatic lipid metabolism and to prevent hepatic lipid accumulation in a mouse model of cancer ( 43 ). Our data show that Indo blunts the accumulation of CE and TG in the liver.…”
Section: Discussionmentioning
confidence: 59%
“…Although FO is a well-known lipid-lowering agent, the effect of Indo in modulating lipid metabolism has not been clearly elucidated. As for hepatic steatosis, Indo was shown to increase hepatic lipid metabolism and to prevent hepatic lipid accumulation in a mouse model of cancer ( 43 ). Our data show that Indo blunts the accumulation of CE and TG in the liver.…”
Section: Discussionmentioning
confidence: 59%
“…Meanwhile, there is no evidence of hepatocellular hypertrophy at P21 and P60. This fi nding further suggests that indomethacin may have triggered a cell proliferation as a regenerative response (17) as confi rmed by higher liver and body weight and the liver to body weight ratios in 25 mg/kg indomethacin.…”
Section: Tab 3 Effect Of Early Postnatal Exposure To Indomethacin Omentioning
confidence: 86%
“…Many developmental effects of indomethacin have been described (17). Nagai et al revealed that administration of very low dose (1.3 mg ip) of indomethacin to male rat pups daily on postnatal days 4-13 caused an abnormal lung structure with diminished alveolar air, increased alveolar duct air, increased mean linear intercept, increased septal wall thickness and diminished the number of alveolar crests (14).…”
Section: Tab 3 Effect Of Early Postnatal Exposure To Indomethacin Omentioning
confidence: 99%
See 2 more Smart Citations